The challenge of sustainability in agricultural systems - Bogoviz, Aleksei V. (Lecture Notes in Networks and Systems, 2021)
This book presents a multidisciplinary collection of original contributions made by the leading scholars and practitioners on researching, building, and maintaining sustainable agricultural systems. Being the first of its kind, the book is divided into two volumes. This book presents a comprehensive and informed review of the current state of multidisciplinary knowledge on sustainability in agriculture. The gaps in the scholarly literature are identified and rigorously analyzed, presenting a clear picture of the promising research directions. The authors critically analyze the very concept of sustainable agricultural systems, primarily focusing on the interactions existing between their integral components and with external environments. Relying on the provisions of complex systems science, the scholars then discuss the best approaches and methodologies used to build a comprehensive understanding of agricultural systems, with relation to achieving and maintaining their sustainability. More than that, this book holds two rich sections on (1) agricultural economics and (2) rural sustainability. Understanding sustainable development as a movement toward clearly defined and measurable goals, a set of chapters explore those policies, practices, technologies, and management systems that have an impact on the sustainability of agricultural systems. Agricultural sustainability is an urgent issue to be addressed, and this book makes a unique contribution. Due to its practical focus, the book appeals to practitioners and policymakers working in agricultural economics, governance, and sustainability, not just academics. This is also a valuable resource for graduate students interested in agricultural systems, sustainability, as well as complex systems theory and practice.